Dynamics and Trends of Political Communication Research in the Information Technology Landscape: Bibliometric Analysis with VOSviewer - Astriana Baiti Sinaga; Rayung Wulan (DAWUH : Islamic Communication Journal, 2026)
This study aims to analyze the dynamics and trends of political communication research in the information technology landscape through a bibliometric approach. Data were obtained from the Scopus database with selection criteria consisting of journal articles and proceedings published between 2016 and 2026 using Publish or Perish 8. The analysis process was carried out through the stages of data collection, filtering based on relevance, and mapping and visualization using VOSviewer software. The analysis focused on publication patterns, author collaborations, and the development of emerging research themes. The results show that political communication studies have experienced significant developments along with the rapid transformation of information technology, particularly related to social media, disinformation, and digital political participation. The bibliometric map indicates the existence of main clusters reflecting the research focus on issues of digital democracy, platform-based political campaigns, and the influence of algorithms on public opinion. Furthermore, recent trends point to the integration of technologies such as big data and artificial intelligence in political communication analysis. These findings contribute to identifying future research directions and open up opportunities for developing more interdisciplinary and contextual studies. This research contributes to identifying future research directions that are more technology-based.